Integrating disaster education into geography curriculum: Strengthening school-based preparedness - Kurniawan, Nandi; Saipiatuddin; Hidayaht, Achmad Nur (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Sukabumi Regency is an area prone to natural disasters in West Java. Its location on the south coast, its mountainous and hilly morphology makes Sukabumi Regency prone to earthquakes, tsunamis and landslides. The aim of this research is to illustrate how geography subjects in schools can be a source of disaster education that supports school-based disaster preparedness. Methods: Using a qualitative approach, this study involved in-depth interviews, observations, and document evaluations at Public Senior High School 1 Warung Kiara, with geography teachers as the main informants. Data analysis was carried out through reduction, verification, and drawing conclusions, with local wisdom-based studies to improve learning materials before validation. Findings: Disaster education in schools plays an important role in improving student preparedness through integration into the geography curriculum, social activities, and mitigation training. Although there are challenges in delivering the material, a geographic literacy-based approach, disaster simulations, and partnerships with stakeholders can strengthen understanding and build a culture of preparedness. In addition, expanding disaster education through extracurricular activities such as scouting and the juvenile red cross can provide students with more in-depth practical experiences. Conclusion: The geography subject plays a crucial role in disaster education by enhancing students' awareness and preparedness for disaster risks. Through theoretical and practical approaches such as disaster simulations, risk mapping, and geographic information systems technology, students develop essential mitigation skills. Integrating multidisciplinary perspectives further strengthens school-based disaster preparedness efforts. Novelty/Originality of this article: The novelty of this research lies in illustrating how geography subjects in schools, combined with extracurricular activities, can effectively support disaster education and preparedness, especially in disaster-prone areas like Sukabumi Regency.